Multiscale Experimental Characterization and Computational Modeling of the Human Aorta - Dalbosco, Misael; Haspinger, Daniel Ch.; Li, Kewei; Murtada, Sae Il; Pukaluk, Anna; Rolf-Pissarczyk, Malte; Sherifova, Selda; Sommer, Gerhard (Solid (Bio)mechanics: Challenges of the Next Decade: A Book Dedicated to Professor Gerhard A. Holzapfel, 2022)
Advanced imaging techniques, novel experimental approaches and sophisticated computational modeling frameworks to characterize and simulate the mechanical behavior of soft biological tissues have dramatically improved in the past decades. Particularly, the advancing of multiphoton microscopy and other imaging techniques has enabled a detailed three-dimensional visualization of the underlying microscopic structure of various biological tissues including arterial walls. In addition, mechanical testing combined with sophisticated microscopy techniques allowed us to quantify the tissue microstructural reorganization and the mechanical response under large deformation simultaneously. Multiscale constitutive models incorporating detailed microstructural information such as the 3D dispersion of collagen fibers in the extracellular matrix and experimentally-derived tissue material properties have been developed and employed in the computational simulations of human aortic tissues under various (patho)physiological conditions. Thus, in this chapter, we review some of the most critical advances and developments in experimental approaches and computational modeling strategies to characterize the mechanical behavior of human aortic tissue. In addition, we discuss future challenges to improve our understanding of the aortic tissue and its related pathologies.
Created from Fastlane, Scopus look-up